A damage identification method for connections of adjacent box-beam bridges using vehicle–bridge interaction analysis and model updating. (1st February 2021) - Zhan, Jiawang; Zhang, Fei; Siahkouhi, Mohammad; Kong, Xuan; Xia, He
Highlights: A quantitative damage identification method is proposed for adjacent box beam connections. Coherence function of the response spectrum is sensitive to the connection damage. The proposed method depends less on parameters such as vehicle speeds and road roughness levels. Abstract: This paper presents a method to locate and quantitatively evaluate the hidden damage in adjacent box-beam connection (ABBC) of precast prestressed concrete (PC) box-beam bridges using the vehicle-bridge interaction analysis and the model updating method. To assess the defects in ABBCs, damage indices are defined based on the cracking height and the residual bending stiffness. The coherence function of the response spectrum (CFRS) indices are calculated for all ABBCs, and the objective function is constructed using the CFRS index and frequency residual vectors. Through a numerical study, this paper shows that the proposed identification method is relatively insensitive to factors such as vehicle speed, passing path, vehicle type, road roughness levels, bridge boundary conditions and their uncertainties, shows that various cases with different damage locations and severities can accurately be evaluated. The proposed method is also verified by the field measurements (before and after bridge repair). The identified damage indices before repair show that the total cracking state of ABBCs is in good agreement with the in-situ inspection results. Furthermore, the evaluation results after repair indicate that the proposed method can correctly identify the current damage of the bridge and is insensitive to the vehicle speed and passing path. The comparison of damage indices before and after repair proves that the ABBCs are in good condition due to effective strengthening. By both the numerical simulation and field evaluation test, it is demonstrated that the proposed method can effectively evaluate the damage conditions of ABBCs without interrupting the normal traffic.